Long‐read genome assembly and genetic architecture of fruit shape in the bottle gourd. (5th July 2021) - Xu, Pei; Wang, Ying; Sun, Fengshuo; Wu, Rongling; Du, Huilong; Wang, Yuhong; Jiang, Libo; Wu, Xiaohua; Wu, Xinyi; Yang, Liming; Xing, Nailin; Hu, Yaowen; et al.
SUMMARY: The bottle gourd ( Lagenaria siceraria, Cucurbitaceae) is an important horticultural crop exhibiting tremendous diversity in fruit shape. The genetic architecture of fruit shape variation in this species remains unknown. We assembled a long‐read‐based, high‐quality reference genome (ZAAS_Lsic_2.0) with a contig N50 value over 390‐fold greater than the existing reference genomes. We then focused on dissection of fruit shape using a one‐step geometric morphometrics‐based functional mapping approach. We identified 11 quantitative trait loci (QTLs) responsible for fruit shape (fsQTLs), reconstructed their visible effects and revealed syntenic relationships of bottle gourd fsQTLs with 12 fsQTLs previously reported in cucumber, melon or watermelon. Homologs of several well‐known and newly identified fruit shape genes, including SUN, OFP, AP2 and auxin transporters, were comapped with bottle gourd QTLs. Significance Statement: This work provides a long‐read‐based, high‐quality reference genome (ZAAS_Lsic_2.0) with a contig N50 value over 390‐fold greater than the existing reference genomes. It also dissects the genetic architecture of fruit shape using a one‐step geometric morphometrics‐based functional mapping approach. This study provides rich resources for the cucurbit community and sheds new light on fruit shape biology in plants.